Blastocyst-Derived Lactic Acid May Regulate S100A6 Expression and Function in Mouse Decidualization via Stimulation of Uterine Epithelial Arachidonic Acid Secretion - Meng-Yuan Li; Ying Wang; Ying Wu; Xu-Yu Zhao; Zhen-Shan Yang; Bo Li; Si-Ting Chen; Yu-Ying He; Zeng-Ming Yang (Cells, 2024)
(1) Background: Inflammatory responses are implicated in embryo implantation, decidualization, pregnancy maintenance and labor. Both embryo implantation and decidualization are essential to successful pregnancy in rodents and primates. S100A6 is involved in inflammation, tumor development, apoptosis and calcium homeostasis. S100A6 is strongly expressed in mouse decidua, but the underlying mechanisms of how S100A6 regulates implantation and decidualization are poorly defined. (2) Methods: Mouse endometrial stromal and epithelial cells are isolated from day 4 pseudopregnant mouse uteri. Both immunofluorescence and Western blotting are used to analyze the expression and localization of proteins. The molecular mechanism is verified in vitro by Western blotting and the quantitative polymerase chain reaction. (3) Results: From days 4 to 8 of pregnancy, S100A6 is specifically expressed in mouse subluminal stromal cells. Blastocyst-derived lactic acid induces AA secretion by activating the luminal epithelial p-cPLA2. The epithelial AA induces stromal S100A6 expression through the COX2/PGI2/PPAR δ pathway. Progesterone regulates S100A6 expression through the progesterone receptor (PR). S100A6/RAGE signaling can regulate decidualization via EGFR/ERK1/2 in vitro. (4) Conclusions: S100A6, as an inflammatory mediator, is important for mouse implantation and decidualization.